Advances in treatment formulations for acute myeloid leukemia. Issue 12 (December 2018) - Briot, Thomas; Roger, Emilie; Thépot, Sylvain; Lagarce, Frederic
Highlights: Few new active drugs are proposed to treat acute myeloid leukemias. New formulations can change the efficiency of old drugs. Nanomedicine can help to target the disease. The residence time in the body is also impacted by new formulations. New formulations appeared very recently in clinical trials and on the market. Abstract : Acute myeloid leukemia (AML) is the most common cause of leukemia-related mortality. The combination of cytarabine and anthracycline has been the gold standard of treatment over the past 40 years, but the distribution of the drugs in the body leads to severe adverse effects. Poor prognosis of older patients with AML is the consequence not only of comorbidities, but also of chemoresistance resulting from frequent secondary AML. Numerous strategies using nanotechnologies are in development to improve drug targeting, pharmacokinetics, administration route, chemoresistance, and adverse effects generally observed. Among the four new drugs approved for AML by the US Food and Drug Administration (FDA) in 2017, Vyxeos ® is a novel liposomal formulation of historical AML drugs. Here, we review current AML treatments and discuss how the development of new formulations will change the therapeutic armamentarium. Teaser: This review presents current treatments generally used in acute myeloid leukemia therapy, and highlights innovative formulations designed to overcome drug resistance or adverse effects observed with current treatments.